Upper airway stimulation for obstructive sleep apnea: durability of the treatment effect at 18 months - Strollo, Patrick J., Jr.; Maurer, Joachim T. (Sleep, 2015)
Objective:To determine the stability of improvement in polysomnographic measures of sleep disordered breathing, patient reported outcomes, the durability of hypoglossal nerve recruitment and safety at 18 months in the Stimulation Treatment for Apnea Reduction (STAR) trial participants.Design:Prospective multicenter single group trial with participants serving as their own controls.Setting:Twenty-two community and academic sleep medicine and otolaryngology practices.Measurements:Primary outcome measures were the apnea-hypopnea index (AHI) and the 4% oxygen desaturation index (ODI). Secondary outcome measures were the Epworth Sleepiness Scale (ESS), the Functional Outcomes of Sleep Questionnaire (FOSQ), and oxygen saturation percent time < 90% during sleep. Stimulation level for each participant was collected at three predefined thresholds during awake testing. Procedure- and/or device-related adverse events were reviewed and coded by the Clinical Events CommitteeResults:The median AHI was reduced by 67.4% from the baseline of 29.3 to 9.7/h at 18 mo. The median ODI was reduced by 67.5% from 25.4 to 8.6/h at 18 mo. The FOSQ and ESS improved significantly at 18 mo compared to baseline values. The functional threshold was unchanged from baseline at 18 mo. Two participants experienced a serious device-related adverse event requiring neurostimulator repositioning and fixation. No tongue weakness reported at 18 mo.Conclusion:Upper airway stimulation via the hypoglossal nerve maintained a durable effect of improving airway stability during sleep and improved patient reported outcomes (Epworth Sleepiness Scale and Functional Outcomes of Sleep Questionnaire) without an increase of the stimulation thresholds or tongue injury at 18 mo of follow-up.
Gesehen am 27.03.2018